Aberrant Migratory Behavior of Immune Cells in Recurrent Autoimmune Uveitis in Horses - Wiedemann, Carmen; Amann, Barbara; Degroote, Roxane L.; Witte, Tanja; Deeg, Cornelia A. (Frontiers in Cell and Developmental Biology, 2020)
The participating signals and structures that enable primary immune cells migrating within dense tissues are not completely revealed until now. Especially in autoimmune diseases, mostly unknown mechanisms facilitate autoreactive immune cells to migrate to endogenous tissues, infiltrating and harming organ-specific structures. In order to gain deeper insights into migratory behavior of primary, autoreactive immune cells, we examined peripheral blood-derived lymphocytes (PBL) of horses with equine recurrent uveitis (ERU), a spontaneous animal model for autoimmune uveitis in humans. In this study, we used a three-dimensional collagen I hydrogel matrix and monitored live-cell migration of primary lymphocytes as a reaction to different chemoattractants such as fetal calf serum (FCS), cytokines IL-4 and IFN-γ and a specific uveitis autoantigen, cellular retinaldehyde binding protein (CRALBP). Through these experiments, we uncovered distinct differences between PBL from ERU cases and PBL from healthy animals, with significantly higher cell motility, cell speed and straightness during migration of PBL from ERU horses. Furthermore, we emphasized the significance of expression levels and cellular localization of septin 7, a membrane-interacting protein with decreased abundance in PBL of autoimmune cases. To underline the importance of septin 7 expression changes and the possible contribution to migratory behavior in autoreactive immune cells, we used forchlorfenuron (FCF) as a reversible inhibitor of septin structures. FCF treated cells showed more directed migration through dense tissue and revealed aberrant septin 7 and F-actin structures along with different protein distribution and translocalization of the latter, uncovered by immunochemistry. Hence, we propose that septin 7 and interacting molecules play a pivotal role in the organization and regulation of cell shaping and migration. With our findings, we contribute to gaining deeper insights into migratory behavior and septin 7 dependent cytoskeletal reorganization of immune cells in organ-specific autoimmune diseases.